Understanding the national evidence on the double burden of malnutrition in Ethiopia for the implications of research gap identifications: a scoping review - Lemma Getacher; Tefera Belachew; Beyene Wondafrash Ademe (BMJ Open)
Background Owing to the unavoidable consequences of nutritional transition, the double burden of malnutrition (DBM) is an emerging public health problem. An increasing number of studies have found that Ethiopians face a DBM. However, country-level evidence has not yet been summarised using a scoping review study design.Objective The main objective of this review was to map the national evidence on DBM in Ethiopia for the implications of research gap identifications.Eligibility criteria The population, concept and context approach was used. All age groups, box sexes, all dates of publication and articles in English language focused on DBM conducted in Ethiopia were included.Sources of evidence Primary research articles, systematic reviews, meta-analyses and scoping reviews searched from electronic databases such as PubMed, ScienceDirect, Cochrane Library, Wiley Online Library, Google Scholar and Google were the sources of evidence.Charting methods The Joanna Briggs Institute Reviewer’s manual was used as a review methodology. The authors, publication year, region, study design, sample size, population group, measured outcomes and main findings were charted in a table.Results A total of 35 articles met the inclusion criteria among 124 426 participants. The average summarised prevalence of DBM was 33.6%, with the average proportions of undernutrition and overnutrition at 21.5% and 12.1%, respectively. The major factors that influenced the DBM were categorised as child, maternal, adolescent, household and adult-related factors.Conclusion In Ethiopia, the overall prevalence of DBM is high, which makes one-third of the population affected by DBM. The foremost determinant factors that influenced the DBM were characterised as child, maternal, adolescent, household and adult-related factors. Therefore, a double-duty interventions should be used to address DBM, considering multilevel factors at the individual, community and societal levels.Protocol registration This review was registered on the figshare website on 28 February 2021, with DOI number https://doi.org/10.6084/m9.figshare.14131874. The review protocol was published with a DOI number http://dx.doi.org/10.1136/bmjopen-2021-050805.